SUSTAINABILITY ECONOMIC AND ECONOMIC GROWTH: THE MODERATING EFFECT OF DISPARITY REGION AND INCOME ON SOCIETY WELFARE - Arief, Sjamsul; Ujianto; Mashudi, Djohan (International Journal of Research -GRANTHAALAYAH, 2018)
This study aims to examine and analyze the influence of regional financial independence, capital expenditure, government investment with moderate effects of disparity between regions and income disparities to economic growth, employment and community welfare. Data analysis method used was Structural Equation Modeling (SEM) with Partial Least Square (PLS) approach, to test the ten hypotheses formulated in this research, then used path analysis (Path Analysis). The conclusions of this study are: (1) Regional financial independence has a positive and significant impact on economic growth, while regional financial independence with moderate effects of disparity between regions has a negative but not significant effect on economic growth. (2) Regional financial independence has a positive and insignificant effect on labor absorption, while regional financial independence with moderate effects of disparity between regions has positive and insignificant effect. (3) Regional financial independence has a positive and significant impact on the welfare of the community. (4) Local government capital expenditure has negative and insignificant effect on economic growth, while regional government capital expenditure with moderate effect of disparity between regions has positive and insignificant effect on economic growth. (5) Local government capital expenditure has negative and insignificant effect on labor absorption, while regional government capital expenditure with moderate effect of disparity between regions has positive and insignificant effect on labor absorption. (6) Local government investment has negative and insignificant effect on economic growth, while local government investment with moderate effect of inter-regional disparity has positive effect not significant to economic growth. (7) Local government investment has a positive and significant effect on labor absorption, while local government investment with moderate effect of disparity between regions has negative and insignificant effect on labor absorption. (8) Economic growth has a positive and significant impact on the welfare of the community, while the economic growth with the effect of moderation income disparity has a positive but insignificant effect on people's welfare. (9) Employment absorption has a negative and significant effect on people's welfare, while employment absorption with moderation effect of income disparity has negative and insignificant effect on people's welfare. (10) Local government investment has a positive and insignificant effect on people's welfare. Increased local government investment spending does not provide much improvement in the welfare of the people.